2021
DOI: 10.1103/physrevc.103.054306
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of magnetic dipole strength in Sn100140 isotope chain and the quenching of nucleon g factors

Abstract: The evolution of electromagnetic transitions along isotope chains is of particular importance for the nuclear structure and dynamics, as well as for the r-process nucleosynthesis. Recent measurement of inelastic proton scattering on even-even 112−124 Sn isotopes provides a novel insight into the isotopic dependence of E1 and M1 strength distributions. We investigate M1 transitions in eveneven 100−140 Sn isotopes from a theoretical perspective, based on relativistic nuclear energy density functional. The M1 tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Theory framework employed in this work follows the formalism based on relativistic energy density functional recently developed in studies of M1 transitions [44][45][46][47][48]. The nuclear ground state represents the basis for studies of excitations, and it is described by employing selfconsistent RHB model as given in Ref.…”
Section: Formalismmentioning
confidence: 99%
“…Theory framework employed in this work follows the formalism based on relativistic energy density functional recently developed in studies of M1 transitions [44][45][46][47][48]. The nuclear ground state represents the basis for studies of excitations, and it is described by employing selfconsistent RHB model as given in Ref.…”
Section: Formalismmentioning
confidence: 99%
“…Numerous theoretical and experimental investigations have been conducted to explore the isotopic sensitivity of both natural parity electric dipole (E 1) and unnatural parity magnetic dipole (M1) responses. These studies revealed a pronounced dependence of dipole strength distributions on the neutronto-proton (N/Z) ratio [21][22][23][24][25][26][27][28][29][30]. Given that nuclei can also exist in extreme conditions within stellar environments, there has been a growing interest in understanding the temperature dependence of nuclear excitations.…”
Section: Introductionmentioning
confidence: 99%